Using the QRS-VHis Interval–based Algorithm to Optimize the Ablation Process of Outflow Tract Premature Ventricular Complexes - Wang, Linlin; Wang, Lei; Liu, Hailei; Wu, Nan; Cheng, Kuan; Wang, Yunlong; Wang, Yuegang; Xiao, Fangyi; Jiang, Ruhong; Zhu, Xuefeng; Chen, Jingcheng; Wang, Jinfeng; et al. (Canadian journal of cardiology, 2025)
The choice between left- and right-sided ablation for outflow tract premature ventricular complexes (OT-PVCs) during procedures remains a topic of ongoing discussion. In this study we aim to elucidate the value of the QRS-VHis interval in distinguishing between left and right origins in left bundle branch block (LBBB)-type OT-PVCs, thereby optimizing the ablation process. The QRS-VHis interval was measured in consecutive patients with LBBB-type OT-PVCs. The performance of this interval was compared with traditional electrocardiographic (ECG) algorithms and prospectively validated in a cohort from 8 centers. Based on the interval, we developed an algorithm to assess its efficacy in optimizing the ablation process. A total of 166 patients were enrolled in the development cohort, and 53 patients in the validation cohort. The QRS-VHis interval demonstrated greater accuracy than ECG algorithms among 153 patients with typical endocardial origins (area under the curve = 0.962). At a cutoff of 30 ms, the QRS-VHis interval showed a sensitivity of 71.8% and a specificity of 98.2% for identifying left-sided locations. A flowchart was developed based on the QRS-VHis interval, indicating that a QRS-VHis value of < 30 ms necessitated left-sided ablation with a 94% likelihood, leading to an 88% success rate. Conversely, when the QRS-VHis value was ≥ 30 ms, the likelihood of requiring left-sided ablation dropped to only 16%. The accuracy of the flowchart was validated in the independent cohort. The QRS-VHis interval is superior for distinguishing between left and right ventricular outflow tract origins in LBBB-type OT-PVCs and has proven valuable in optimizing the intraprocedural process. Le choix entre l'ablation du côté gauche et du côté droit pour les complexes ventriculaires prématurés du tractus de sortie (CVP-TS) pendant les procédures reste un sujet de discussion en cours. Cette étude vise à élucider la valeur de l'intervalle de temps compris entre le début du complexe QRS jusqu'au faisceau de His (QRS-VHis) dans la distinction entre les origines gauche et droite des CVP-TS de type bloc de branche gauche (BBG), optimisant ainsi le processus d'ablation. L'intervalle QRS-VHis a été mesuré chez des patients consécutifs présentant des CVP-TS de type BBG. L'efficacité de cet intervalle a été comparée aux algorithmes ECG traditionnels et validée prospectivement dans une cohorte de 8 centres. Sur la base de cet intervalle, nous avons développé un algorithme pour évaluer son efficacité dans l'optimisation du processus d'ablation. Au total, 166 patients ont été enrôlés dans la cohorte de développement et 53 dans la cohorte de validation. L'intervalle QRS-VHis a démontré une plus grande précision que les algorithmes ECG chez 153 patients avec des origines endocardiques typiques (aire sous la courbe = 0,962). Avec un seuil de 30 ms, l'intervalle QRS-VHis a montré une sensibilité de 71,8 % et une spécificité de 98,2 % pour l'identification des emplacements du côté gauche. Un organigramme a été élaboré sur la base de l'intervalle QRS-VHis, indiquant qu'une valeur QRS-VHis inférieure à 30 ms nécessitait une ablation du côté gauche avec une probabilité de 94 %, conduisant à un taux de réussite de 88 %. À l'inverse, lorsque la valeur QRS-VHis était supérieure ou égale à 30 ms, la probabilité d'une ablation du côté gauche ne s'élevait plus qu'à 16 %. La précision de l'organigramme a été validée dans une cohorte indépendante. L'intervalle QRS-VHis s'est montré supérieur pour distinguer les origines des CVP-TS de type BBG, par la voie d'éjection du ventricule gauche ou la voie d'éjection du ventricule droit, et s'est avéré précieux pour optimiser le processus intraprocédural. [Display omitted]